INOVASI DALAM PROGRAM STEM SEKOLAH: ANALISIS BIBLIOMETRIC EKSTRAKURIKULER ROBOTIKA DAN DAMPAKNYA TERHADAP KETERAMPILAN KREATIF - Astuti, Lis; Triyanto, Triyanto; Karsono, Karsono (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
Although extracurricular robotics programs have been recognized as a potential approach to developing students' STEM skills, there is still a gap in understanding of the program's development and impact globally. This research aims to analyze the development of robotics-based STEM programs. This research method uses bibliometrics with a focus on publication trends, collaboration patterns, and the evolution of research topics during the 2014-2024 period. Using data from the Scopus database with 2,469 articles analyzed using VOSviewer, the study revealed three main findings: (1) a significant increase in publications on educational robotics since 2020, especially in the journal Education and Information Technologies, (2) the dominance of North American and East Asian institutions in research with an increasingly global trend of collaboration, and (3) the evolution of research focus from technical aspects to a more holistic approach to development Educational Robotics Program. These findings have important implications for the development of more effective and contextual extracurricular robotics programs to improve students' creative skills in STEM learning.